Assessing and managing the impact of duck hunting in Victoria–a new approach - Loyn, Richard H (Wildfowl, 1991)
The impact of duck hunting in Victoria was assessed by comparing the take of game species and the of protected species with initial numbers of birds on large samples of wetlands. Numbers of birds were also measured on these wetlands after the opening weekend and at the end of the season. Estimates of annual production were made by examining samples of bagged ducks. This approach avoids the need to estimate total take or total population. Estimates of total population are expensive and impractical in many parts of the world. The kill of protected species had little impact on numbers of any species except Freckled Duck Stictonetta naevosa. The take of game ducks exceeded annual production until 1990, when hunter numbers halved after introduction of a compulsory video test of their ability to identify water birds. Various other management options have been introduced or considered as part of a general review.